2012
DOI: 10.1111/jai.12072
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of semen in shabout (Barbus grypus Heckel, 1843): sperm motility and fertilization rates

Abstract: Summary The effects of three different dosages of Dimethyl‐sulf‐oxide (DMSO) (7, 10, 15%) were investigated on post‐thaw motility of frozen spermatozoa from the shabout (Barbus grypus H., 1843). Three aliquots were diluted in each DMSO treatment at a final proportion of (10% sperm, 83% glucose extender and 7% DMSO), (10% sperm, 80% glucose extender and 10% DMSO) and (10% sperm, 75% glucose extender and 15% DMSO), respectively. Compared to fresh milt, cryopreserved spermatozoa showed a significant decrease in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…However, the concentration of DMSO used is species-dependent. For example, the best dilution for R. tawarensis was 5% (Muchlisin et al, 2020), 10% for C. carpio (Irawan et al, 2010), and 10% for B. grypus sperm (Dogu, 2012). This study showed the use of a single concentration across all CPAs.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, the concentration of DMSO used is species-dependent. For example, the best dilution for R. tawarensis was 5% (Muchlisin et al, 2020), 10% for C. carpio (Irawan et al, 2010), and 10% for B. grypus sperm (Dogu, 2012). This study showed the use of a single concentration across all CPAs.…”
Section: Discussionmentioning
confidence: 74%
“…DMSO was also suitable for the sperm of depik fish Rasbora tawarensis (Muchlisin et al, 2020), seurukan fish Osteochillus vittatus (Muthmainnah et al, 2018), African catfish Clarias gariepinus (Omitogun et al, 2010), Mugil cephalus (Balamurugan et al, 2019), Barbus grypus (Dogu, 2012), common carp Cyprinus carpio (Irawan et al, 2010), and mahseers Tor tambroides and T. dauronensis (Chew et al, 2010). However, the concentration of DMSO used is species-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…The sperm concentration (×10 9 sperm mL −1 ) of L. chrysophekadion ranged from 8.80 to 18.20 which was in the range values that have been reported for other cyprinid fish such as in Barbus group, 12.45–18.81 for B. barbus (Alavi, Psenicka, Rodina, Policar & Linhart ), 8.60–25.30 in C. idella (Bozkurt, Ogretmen, Ercin & Yildiz ), 9.80–20.20 for B. sharpeyi (Alavi, Jorfi et al . ), 13.30–34.80 in Vimba vimba (Alavi, Kozak, Hatef, Hamackova & Linhart ), 19.38 ± 2.89 for Barbus grypus (Dogu ) and 16.96–18.81 in C. carpio (Cejko, Krejszeff, Judycka, Sarosiek, Dietrich, Kucharczyk & Kowalski ) (Table ). Differences in spermatozoa concentration among species might be due to the frequency of stripping and spermiation induction (Billard, Cosson, Crim & Suquet ).…”
Section: Discussionmentioning
confidence: 99%
“…The aim of B. grypus cultivation is the production of fingerlings for restocking dam lakes and the production of cultured fish broodstocks. Although there is a cryopreservation study (20), there is little information about B. grypus sperm, especially sperm activation, and it has not been previously studied. Although information on the basic reproductive biology of this species is available, the effect of pH and cations on spermatozoa motility is unknown.…”
Section: Introductionmentioning
confidence: 99%